PHARMACORESISTANT FORMS OF EPILEPSY WITH LONG-TERM USE OF ANTIEPILEPTIC DRUGS IN WOMEN OF FERTILE AGE. (Modern education and development, 2025)
The gold standard in diagnosing epilepsy as well as predicting its clinical course is the electroencephalographic (EEG) examination method, which indicates the functioning of brain neurons and their excitability, which makes it possible to diagnose an epileptic focus. EEG is performed on patients with suspected or already diagnosed seizures to identify the type of epilepsy. The sensitivity of EEG for epilepsy is up to 50%; in 10% of epileptic patients epileptiform activity is not recorded.